PERAN GURU BIMBINGAN DAN KONSELING DI SEKOLAH PADA MASA NEW NORMAL - Fenny Adnina Daulay (UIN Kiai Haji Achmad Siddiq Jember, 2022)
At this time the situation of the spread of Covid-19 in Indonesia can be said to be stable and under control. However, face-to-face meetings (PTM) activities are still limited. The purpose of this paper is to obtain information about the role of teachers in the implementation of BK during the pandemic to the current endemic period. Information is collected by conducting a literature study by At this time the situation of the spread of Covid-19 in Indonesia can be said to be stable and under control. However, face-to-face meetings (PTM) activities are still limited. The purpose of this paper is to obtain information about the role of teachers in the implementation of BK during the pandemic to the current endemic period. Information is collected by conducting a literature study by collecting literature material which is then presented in the form of a narrative. The role of Guidance and Counseling teachers in schools during the Covid-19 period is very crucial in helping students in assisting students in various problems faced during learning until the PTM period which is still limited in meeting time.collecting literature material which is then presented in the form of a narrative. The role of Guidance and Counseling teachers in schools during the Covid-19 period is very crucial in helping students in assisting students in various problems faced during learning until the PTM period which is still limited in meeting time.